Implantation of a New Productive Layout in a Company of Lubricants and Degreasers Sector (Research, Society and Development, 2019)
Amid a highly competitive scenario among companies, any cost reduction becomes critical to survival. One of the main points that can be analyzed and improved the layout, which encompasses from the installation of machines, equipment, stocks, to areas of circulation. The methodology used was a field survey, survey of the current layout, the preparation of projects in 2D and 3D format to identify the time of production and movement by comparative means and the stock of raw material. The results showed a reduction of 51,19% in the production and handling time, reducing the production bottleneck, the current and proposed layout change showed significant changes as equipment approximation,  the rational use of the manufacturing space of industrial lubricants and degreasers, administrative and inventory organization.